The Engineering Design and Prototyping of an Auxiliary Standing Toilet Chair Driven by Electric Cylinders - Long-Chang Hsieh; Tzu-Hsia Chen; Po-Cheng Lai; Tsung-Ming Huang (Machines)
As physical capabilities decline with age, elderly individuals often require assistance from others when using the toilet. An auxiliary standing toilet chair can enhance convenience for the elderly, allowing them to use the toilet independently. Commercially available auxiliary standing toilet chairs and related patents share common issues, such as seat link rotation angles of less than 45° and a high driving force requirement. This study categorizes four-bar linkages into three design concepts and then carries out a kinematic design process based on the design requirements and constraints of the auxiliary standing toilet chair. Three feasible design examples were developed, followed by motion simulations and driving force analyses using INSPIRE 2019.2 software. In Design Example I, an actuator directly drives the seat link, rotating the seat to 48°. The required driving force for a 150 kg user is reduced from 6070 N to 2258 N, representing a 62.35% reduction in the required force.